All-in-One Pediatric Parenteral Nutrition Admixtures with an Extended Shelf Life—Insight in Correlations between Composition and Physicochemical Parameters - Gostyńska, Aleksandra (Pharmaceutics, 2021)
The administration of three-in-one parenteral nutrition (PN) admixtures to pediatric patients requires special consideration, specifically concerning quality and physicochemical stability. The introduction of a new parenteral amino acid solution into the market prompted us to evaluate Aminoplasmal Paed-based PN admixtures’ stability. The study aimed to determine the physicochemical parameters of the chosen variations of PN admixtures and search for a correlation between its composition and those parameters. One hundred and sixty-eight variations of PN admixtures intended for patients weighing from 10 to 25 kg and aged from 1 to 12 years and differing in the quantitative composition of electrolytes were selected for the study. The samples were prepared using each of the four intravenous lipid emulsions dedicated to pediatric patients: Intralipid 20%, Clinoleic 20%, Lipidem 20%, and Smoflipid 20%. The stability of the PN admixtures was assessed by visual inspection and determination of pH, osmolality, zeta potential, and hydrodynamic mean droplet diameter (MDD) immediately upon preparation and after seven days of storage at the temperature of 5 ± 1 °C with light protection. Pearson’s correlation was used to quantify the relationships between selected ingredients of the PN admixtures and the physicochemical parameters. The PN admixtures were characterized by pH ranging from 5.91 to 7.04, osmolality ranging from 1238 to 1678 mOsm/kg, and zeta potential ranging from −41.3 to −2.16 mV. The changes in pH and osmolality after seven days of storage did not exceed 0.2 and 4.4%, respectively. The homogeneity of the PN admixtures was confirmed by determining the polydispersity index, which ranged from 0.06 to 0.2. The MDD of the studied formulas ranged from 235 to 395 nm and from 233 to 365 nm immediately upon preparation and after the storage period, respectively. Correlations between selected components of the PN admixtures and some physicochemical parameters were found. All Aminoplasmal Paed 10%-based PN admixtures were characterized by appropriate physicochemical quality to be administered via the central veins, both immediately upon preparation and after seven days of storage at the temperature of 5 ± 1 °C with light protection. The applied electrolyte concentrations ranges and types of lipid emulsions in the selected macronutrient quantitative compositions allowed the PN admixtures to remain stable for seven days within the specified limits.